COMPARATIVE STUDIES ON NUTRITIONAL AND PESTICIDES RESIDUE IN ORGANIC AND CONVENTIONALLY GROWN BLACK WHEAT IN THE SHEKHAWATI REGION OF RAJASTHAN (International Journal of Food and Nutritional Sciences, 2025)
Objectives: This present study aims to compare the nutritional composition, levels of pesticide residues, and environmental impact of organic compared with conventionally grown black wheat in the semi-arid Shekhawati region of Rajasthan.Methods: A samples of black wheat collected from organic and conventional farming were taken from two different regions namely:-Conventinal sample taken from Chainpura region and organic sample taken from Kolida region. Analysis of nutritional parameters includes estimation of protein, fat, fiber, zinc, and calcium. Pesticide residues were quantified by both GC-MS and LC-MS/MS techniques. Soil and water quality also were measured to assess the environmental impacts. Various statistical analyses, such as t-test and PCA, were made to determine significance and find out the clustering patterns.Results: Organic black wheat had higher contents of fibers (8.38%) and zinc (4.79 mg/100g) but had lower contents of proteins (12.96%) and fats (0.73%) than conventional samples. Interestingly, the organic samples did not have any pesticide residues, whereas residues in conventional samples were higher than the maximum allowed residue limit. Environmental indicators showed that organic farming practices have lesser soil salinity, less contamination, and greater nutrient retention compared to conventional farming.